Behavior of grafted orange varieties in different rootstocks in Xalostoc, Morelos - González Hernández, Álvaro; Guillén Sánchez, Dagoberto; Alia Tejacal, Iran; López Martínez, Víctor; Juárez López, Porfirio; Bárcenas Santana, Daniel (Revista Mexicana de Ciencias Agrícolas, 2020)
Citrus groves in Morelos are recent and expanding; however, present technologies are scarce. There are problems due to pathogen attacks and therefore insufficient productivity, so it is necessary to improve the production and profitability of the crop using varieties with better behavior, that have an optimal vegetative development, production and quality of the fruit. The research was carried out during 2016, with the aim of evaluating the behavior and development of four varieties of orange grafted in different patterns, under the edaphoclimatic conditions of East of Morelos. Sixteen rootstock-variety combinations, planted at a planting distance of 7 x 4 m, were compared. Agronomic variables were evaluated: stem diameter and plant height, flowering and fruiting, relative chlorophyll content, height and crown diameter. The Volkamerian rootstock combined with the Mars variety reached the largest stem diameter without differences with the other varieties. When the Jaffa, Hamlin and Mars varieties were used on this pattern, the trees with the highest growth as well as the highest height and diameter of the crown were obtained. The Jaffa variety on Volkamerian had the highest number of flowers and fruits, as well as the highest leaf chlorophyll content. The smallest, least leafy trees with thin trunks and the least number of flowers and fruits were those achieved on the Naranjo Agrio pattern.